Resistance and Ambivalence in the Novel Bumi Manusia by Pramoedya Ananta Toer - Najib, Muhammad Rifqi Ainun; Supriyanto, Teguh; Doyin, Mukh (Universitas Negeri Semarang, 2023)
The novel Bumi Manusia is played by characters with strong character and strong principles. With such a character and faced with a shackling situation, these characters naturally resisted. However, ambivalence is sometimes present in every resistance. In this research, the researchers determined the data in the form of words, phrases, and others contained in Bumi Manusia and suspected of containing resistance and ambivalence. The data was collected using heuristic technique. After all the data had been collected, the researcher used hermeneutic techniques as a tool for analysis. Using these techniques, the researcher found that Bumi Manusia was a novel that told about the topics of the ‘45 generation including patriarchism, colonialism, and the like. The various forms of subordinates, by many characters, were then responded to with various resistances, both public and hidden. However, not all resistance produced in a perfect form. At some point, resistance would produce ambivalence. In this study, researchers found some resistance data which were also accompanied by ambivalence.